Design and Cryptanalysis of a New Encryption Algorithm SAFER-256 - Khachatrian, Gurgen H.; Kyureghyan, Melsik K.; Kyuregyan, Knarik M. (Mathematical Problems of Computer Science, 2021)
In this paper a new encryption algorithm of SAFER family named SAFER-256 is introduced. SAFER-256 is a 256 bit size block cipher with a 256 bit size user selected key. Security of the new algorithm against differential analysis attack is also presented.